2006
DOI: 10.1039/b606052h
|View full text |Cite
|
Sign up to set email alerts
|

Supported phospholipid bilayer formation on hydrophilicity-controlled silicon dioxide surfaces

Abstract: We investigated the influence of surface hydroxyl groups (-OHs) on the supported planar phospholipid bilayer (SPB) formation and characteristics. We prepared SiO2 surfaces with different hydrophilicity degree by annealing the SiO2 layer on Si(100) formed by wet chemical treatments. The hydrophilicity reduced with irreversible thermal desorption of -OHs. We formed SPB of dimyristoylphosphatidylcholine on the SiO2 surfaces by incubation at a 100-nm-filtered vesicle suspension. The formation rate was faster on le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
116
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 84 publications
(123 citation statements)
references
References 85 publications
6
116
1
Order By: Relevance
“…The residual trace the photobleached structure is because of the immobile fraction in the SLB. The majority of the SLB on the PVC membrane was continuous, but not perfect, and a part of the SLB existed as isolated SLB patches, or trapped by the 19,28 PVC surface. The size of the isolated SLB patches was submicron, below the resolution of the optical microscope.…”
Section: Supported Lipid Bilayer On the Pvc Membranementioning
confidence: 99%
See 3 more Smart Citations
“…The residual trace the photobleached structure is because of the immobile fraction in the SLB. The majority of the SLB on the PVC membrane was continuous, but not perfect, and a part of the SLB existed as isolated SLB patches, or trapped by the 19,28 PVC surface. The size of the isolated SLB patches was submicron, below the resolution of the optical microscope.…”
Section: Supported Lipid Bilayer On the Pvc Membranementioning
confidence: 99%
“…Previous studies by R. Tero et al showed that the SLB of dimyristoylphosphatidylcholine was formed on the thermally treated SiO 2 /Si substrate with WCA of 67°C, but the SLB has small pits and defects. 19,28 Detailed analysis about the microscopic structures of the PVC membrane and the SLB on it is a subject for the future study. Topographic and viscoelastic mapping using atomic force microscope, and high-speed single molecule tracking 30 will provide the valuable information about the structure and dynamics of SLB on the micrometer to submicrometer scales.…”
Section: Supported Lipid Bilayer On the Pvc Membranementioning
confidence: 99%
See 2 more Smart Citations
“…Recently, supported lipid bilayers (SLB) are attracting a considerable attention in terms of general interests both as a fluidic membrane supported on a solid surface and as various applications such as biosensors [4]. For realizing biological devices, it is often important to control the spatial patterning of the SLB that has been achieved by various methods, such as using pre-patterned substrates [5], stamping [6], or photo-lithography [7]. However, the patterned structures fabricated by these techniques do not effectively utilize the lateral fluidity of the SLBs.…”
Section: Introductionmentioning
confidence: 99%